File audit to assess sustained fidelity to a recovery and wellbeing oriented mental health service model: an Australian case study - Cara L. Jones; Frank P. Deane; Keren Wolstencroft; Adam Zimmermann (BMC, 2019)
Abstract Background Over the past decade there has been increasing attention to implementing recovery-oriented approaches within mental health service practice and enhancing fidelity to such approaches. However, as is often the case with evidence-based practices, less attention has been paid to the sustainability of recovery-oriented approaches over time. This study sought to investigate whether fidelity to a recovery-oriented practice framework - the Collaborative Recovery Model could be sustained over time. Method The study setting was an Australian community managed mental health organisation. A file audit of consumer support plans was undertaken using the Goal and Action Plan Instrument for Quality audit tool (GAP-IQ). The audit tool assessed 17 areas for quality. Consumers (n = 116) from a large community managed mental health organisation participated in the study. Sustained fidelity to the Collaborative Recovery Model (CRM) was determined by comparing results from the file audit to a similar audit conducted 3 years earlier. Results The file audit revealed a significant increase in fidelity to CRM practices between 2011 and 2014. Fidelity to individual audit items that comprise the GAP-IQ was also found to significantly increase across 16 of the 17 GAP-IQ audit items, with the exception of the 'Action Plan Review' audit item. Conclusions A comparison of file audit data across different time points within the same setting can provide useful feedback about whether or not a practice is being sustained over time. Although fidelity increased overtime the study design does not allow conclusions that training and coaching practices implemented by the organisation were responsible.